Development of virtual experiments based on Adobe Flash - Comina Bellido, Yuri German (2015)
In this work the development of two virtual experiments using Adobe Flash has been reported. The first virtual experiment is based on a mass-spring mechanical system, with which the students can calculate the value of earth gravity, including the measurement error. The second virtual experiment helps students to visualize complex mechanical movements, and also lead them in to the concept of lagrangian mechanics as well as eigen values, vectors and eigen states of a system. In this experiment the mechanical system is composed by three masses and four springs. Both programs are interactive, so the students can change different parameters and therefore visualize changes in the physical ensemble. This fact enables physic teachers to use them as learning tools in an interactive class. The compiled programs can run standalone using free Adobe Flash player or through a webpage. In this last case, students from all over the world can use these tools at the same time.